Sharing intangible cultural heritage: disparities of distribution. Issue 4 (3rd July 2020) - Dippon, Peter; Moskaliuk, Johannes
ABSTRACT: The UNESCO Conventions for the Protection of the material World Heritage (1972) and for the Preservation of the Intangible Cultural Heritage of Humanity (ICH) (2003) use the listing practice for worldwide identification and global recognition. Listing their ICH on the Representative List (RL) lends prestige to the States Parties and enables economic exploitation. Thematic imbalances and spatial disparities arising from the listing of material heritage have already been discussed and analysed in the scientific literature. After more than a decade and more than 500 inscriptions in the framework of the convention for the safeguarding of the intangible cultural heritage (ICHC) of 2003, this article will try for the first time to examine which regions and States Parties have so far been able to actively participate in the ICHC through listings. The analysis examines the chronological distribution and growth development in the regions after a current global status analysis of the globally distributed ICH on the RL. A distinction is always made between national and multinational inscriptions, between aggregated frequency and spatial distribution, and between these two possibilities. The aim is to demonstrate the extent to which participation in the sense of ICH sharing is possible in the regions and what implications can be derived from the listing practice to date.